2002
DOI: 10.1128/jcm.40.12.4753-4756.2002
|View full text |Cite
|
Sign up to set email alerts
|

New Serological Assay for Detection of Putative Helicobacter pylori Virulence Factors

Abstract: We evaluated a new immunoblot assay (Helicoblot 2.1) for Helicobacter pylori infection and CagA and VacA status by using serum samples from 222 patients. The test accurately detected H. pylori infection and VacA status, but improvements in the interpretation criteria are required before it can be recommended for determination of CagA status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 9 publications
2
37
1
Order By: Relevance
“…Helico Blot 2.1 TM kits reportedly have high sensitivity (99% for both H. pylori and CagA seropositivity) and specificity (98% for H. pylori and 90% for CagA seropositivity) among the Korean population. 13 …”
Section: Epidemiologymentioning
confidence: 99%
“…Helico Blot 2.1 TM kits reportedly have high sensitivity (99% for both H. pylori and CagA seropositivity) and specificity (98% for H. pylori and 90% for CagA seropositivity) among the Korean population. 13 …”
Section: Epidemiologymentioning
confidence: 99%
“…On the other hand, there were no false positive results and therefore the Western-rCagA showed 100% specificity. This is also a good result for the rCagA of this study because the lack of specificity of antiCagA tests has been attributed in part to differences in the CagA antigens used (12,30).…”
Section: Discussionmentioning
confidence: 56%
“…Similarly to that we have previously observed for children (Rocha et al 2000), the assay showed high sensitivity (92.8%) for the diagnosis of the infection in adults. Other authors, employing the same kit (Yamaoka et al 1998, Malaty et al 2002, Park et al 2002 or in-house techniques (Faulde et al 1993, Klaamas et al 1996, Karvar et al 1997, Nilsson et al 1997, Holtmann et al 1998) also reported high sensitivity for the test. In addition, we observed that the sensitivity was similar in patients with duodenal ulcer, gastric carcinoma, and gastritis only.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of antibodies against H. pylori antigens can be evaluated by immunoblotting (Mitchell et al 1996, Aucher et al 1998, Yamaoka et al 1998, Figueiredo et al 2001, Park et al 2002. Although expensive and time-consuming, the test seems to be more sensitive than ELISA, especially when the levels of antibodies are low.…”
mentioning
confidence: 99%
See 1 more Smart Citation